Stylized and Performative Gaze for Character Animation. (6th May 2013) - Pejsa, Tomislav; Mutlu, Bilge; Gleicher, Michael
Abstract: Existing models of gaze motion for character animation simulate human movements, incorporating anatomical, neurophysiological, and functional constraints. While these models enable the synthesis of humanlike gaze motion, they only do so in characters that conform to human anatomical proportions, causing undesirable artifacts such as cross‐eyedness in characters with non‐human or exaggerated human geometry. In this paper, we extend a state‐of‐the‐art parametric model of human gaze motion with control parameters for specifying character geometry, gaze dynamics, and performative characteristics in order to create an enhanced model that supports gaze motion in characters with a wide range of geometric properties that is free of these artifacts. The model also affords "staging effects" by offering softer functional constraints and more control over the appearance of the character's gaze movements. An evaluation study showed that the model, compared with the state‐of‐the‐art model, creates gaze motion with fewer artifacts in characters with non‐human or exaggerated human geometry while retaining their naturalness and communicative accuracy.